In Praise of the Terrestrial Condition - Campillo, Antonio (HannahArendt.net, 2022)
The scientific and philosophical revolution of the 16th and 17th centuries was described by Alexandre Koyré as the passage «from the closed world to the infinite universe», which meant the unification of the celestial and the terrestrial under the same physical-mathematical laws, the conversion of the Earth into a planet like any other and the ontological division between the physical order and the human order. However, in the 20th century, the human race acquired for the first time in its history the power to destroy itself, either through nuclear weapons or through a global ecological crisis. At the same time, there has been a paradigm shift in the scientific and philosophical conception of nature and, in particular, of the Earth as the original dwelling place of human beings and other living beings. In this article, all these transformations are analyzed through the ideas of five very different authors: Husserl, Arendt, Lovelock, Margulis and Latour.